After the Long Boom: Living with Capitalism in the Twenty-First Century. Issue 40 (September 2019) - Beynon, Huw
Abstract : This paper reflects on a study of a large chemical plant published over forty years ago and the changes that have taken place in the nature of work and employment in the meantime. It examines the ways in which utopian ideas have influenced accounts of changing workplace relations often associated with the advance of new technologies. The study itself is seen to lie on the cusp of the major transformations reflected in the location of industrial plant, the nature of the division of labour, and the practice of management. Deindustrialization – involving the closure of many manufacturing facilities – is identified as a critical moment opening up other rapid changes in the composition of the labour force and the application of new technologies to new settings in the service economy. Across the period a change of discourse is registered, seen most clearly in the move from ideas of industrialism to those involving capital and labour. The paper documents a spatial, sectoral, and temporal shift in capital, culminating in its penetration of civil society and daily life, creating major questions for social-scientific approaches to industrial relations and for the organizational practices of trade unions.